2009
DOI: 10.1016/j.cattod.2008.09.023
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity of Au nanoparticles supported over SiO2 and TiO2 studied by ambient pressure photoelectron spectroscopy

Abstract: Keywords: Gold, titanium oxide, ambient pressure photoelectron spectroscopy, in situ XPS, model catalysts. AbstractThe influence of the metal cluster size and the identity of the support on the reactivity of gold based catalysts have been studied in the CO oxidation reaction. To overcome the structural complexity of the supported catalysts, gold nanoparticles synthesized from colloidal chemistry with precisely controlled size have been used. Those particles were supported over Si02 and Ti(>2 and their catalyti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
35
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 46 publications
(41 reference statements)
6
35
1
Order By: Relevance
“…106 Herranz et al used this method to adsorb hexadecanethiolstabilised gold colloids (2, 3.7 and 4.8 nm) in chloroform on SiO 2 and TiO 2 (1-2 wt% Au). 107 The elimination of the stabilising agents is indispensable for further uses in gas phase reactions, and sometimes for further reactions in the liquid phase (see Figure 2.5). This is usually performed by calcination treatment.…”
Section: Gold Colloidsmentioning
confidence: 99%
“…106 Herranz et al used this method to adsorb hexadecanethiolstabilised gold colloids (2, 3.7 and 4.8 nm) in chloroform on SiO 2 and TiO 2 (1-2 wt% Au). 107 The elimination of the stabilising agents is indispensable for further uses in gas phase reactions, and sometimes for further reactions in the liquid phase (see Figure 2.5). This is usually performed by calcination treatment.…”
Section: Gold Colloidsmentioning
confidence: 99%
“…Previous studies have shown that the binding of COO À groups to gold surfaces are responsible for the conformation of citrate molecules on gold and silver nanoparticles. 36,51,[54][55][56] Thus, the relative amount of citrate can be estimated by the C1s intensity of the Au-COO À coordinated component at about 288 eV. In Fig.…”
Section: A Centrifugationmentioning
confidence: 99%
“…Different loadings of gold nps can be achieved by changing the concentration of the sol for a given oxide support amount. However, np deposition is usually performed in a non-environment-friendly medium (toluene [19,24], isopropyl ether [18], chloroforme [22,25], methylenechloride [25]), and consequently homogeneous dispersion of these nps on support surface can be a problem since oxide support is hydrophilic [25].…”
Section: Introductionmentioning
confidence: 99%
“…Beyond the classical deposition-precipitation route proposed first by Haruta [9], other methods such as co-precipitation, cosputtering, chemical vapor deposition and grafting were proposed [10][11][12][13][14][15][16][17]. Another less conventional strategy consists in starting from a dispersion of pre-synthesized gold colloidal nanoparticles which are deposited on oxide supports by solvent evaporation [18,19] or vacuum filtration [20][21][22][23]. The advantage of the latter approach comes from the ability to control np size and eventually shape before deposit and minimize the effect of the support on these parameters.…”
Section: Introductionmentioning
confidence: 99%